2018
DOI: 10.1038/s41380-017-0012-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of intellectual disability in consanguineous families

Abstract: Autosomal recessive (AR) gene defects are the leading genetic cause of intellectual disability (ID) in countries with frequent parental consanguinity, which account for about 1/7th of the world population. Yet, compared to autosomal dominant de novo mutations, which are the predominant cause of ID in Western countries, the identification of AR-ID genes has lagged behind. Here, we report on whole exome and whole genome sequencing in 404 consanguineous predominantly Iranian families with two or more affected off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
206
3
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(230 citation statements)
references
References 91 publications
15
206
3
6
Order By: Relevance
“…ROH regions are considered to have functional significance in populations and are considered to be potential target regions having a tendency for rare and common disorders (Magi et al, ). Long ROHs are a consequence of recent parental relatedness and therefore can be observed more frequently in inbred populations, and are more likely to surround causative variants in individuals coming from such populations (Hu et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…ROH regions are considered to have functional significance in populations and are considered to be potential target regions having a tendency for rare and common disorders (Magi et al, ). Long ROHs are a consequence of recent parental relatedness and therefore can be observed more frequently in inbred populations, and are more likely to surround causative variants in individuals coming from such populations (Hu et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Seven families have homozygous variants in potentially novel candidate genes for ARID ( CACNG7, CARNMT1 / C9orf41, EI24, GARNL3, FXR1, TRAPPC10, TET3 ; Tables 1, 2). One additional family MR60 with severe ARID has a homozygous stop variant in GRAMD1B and a rare, damaging mis-sense variant in TBRG1 , both of which lie within the mapped region in chromosome 11q23.2-q24.2 and were previously suggested to be candidate genes for ARID (Reuter et al 2017; Hu et al 2018) having been identified in a single ARID family (Table 2). Both replicated ID genes are likely to be sufficient to cause disease etiology but no conclusion can be made on the impact on the phenotype of being a homozygous carrier for variants in both genes.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous publication a missense variant within GRAMD1B was identified in a consanguineous Syrian family with moderate nonsyndromic ID (Reuter et al 2017). On the other hand, a consanguineous Persian family was found to have a frameshift TBRG1 variant co-segregating with severe ARID and developmental delay (Hu et al 2018). Two out of three affected siblings from family MR60 have severe nonsyndromic ID, but one affected sibling has severe ID with psychomotor delay (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations